A new species of Parachute Gecko (Squamata: Gekkonidae: genus Ptychozoon) from Kaeng Krachan National Park, western Thailand - Sumontha, Montri; Pauwels, Olivier S.g.; Kunya, Kirati; Limlikhitaksorn, Chaiwat; Ruksue, Sirichai; Taokratok, Apirat; Ansermet, Michel; Chanhome, Lawan (Zootaxa, 2012)
A new species of Parachute Gecko, Ptychozoon kaengkrachanense sp. nov., is described from montane evergreen forest in Kaeng Krachan National Park, western Thailand. It differs from all known Ptychozoon species by having three dark dorsal chevrons between limbs insertions, homogeneous dorsal scalation without enlarged scales, original tail without long terminal flap, supranasals widely in contact, a continuous series of 14–19 enlarged precloacofemoral scales, bearing 13–17 pores in males, the absence of a predigital notch in the preantebrachial cutaneous expansion and the presence of cutaneous expansions on sides of head. It is the eighth species described in the genus and the only species of Ptychozoon endemic to Thailand.